2023
DOI: 10.26633/rpsp.2023.55
|View full text |Cite
|
Sign up to set email alerts
|

Health care access and migration experiences among Venezuelan female sex workers living in the Dominican Republic

Abstract: Objective. To identify sexual risk behaviors and barriers to sexual and reproductive health care (SRH) among Venezuelan female sex workers living in the Dominican Republic. Methods. This was a mixed-methods study using four focus group discussions (FGDs) and a cross-sectional quantitative survey with Venezuelan migrant female sex workers. The study was conducted from September through October 2021 in two urban areas (Santo Domingo and Puerto Plata) in the Dominican Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Restrepo Pineda et al found that condom use was not consistent among sex workers and even less likely among Venezuelan male sex workers whose precarious financial situation led them to riskier, yet more profitable, practices ( 30 ). Paulino Ramirez et al exposed feelings of depression and isolation among migrants from Venezuela turning to sex work to survive in the Dominican Republic ( 31 ).…”
Section: Responding To Sensitive Issues Among Migrants: Abortion and ...mentioning
confidence: 99%
“…Restrepo Pineda et al found that condom use was not consistent among sex workers and even less likely among Venezuelan male sex workers whose precarious financial situation led them to riskier, yet more profitable, practices ( 30 ). Paulino Ramirez et al exposed feelings of depression and isolation among migrants from Venezuela turning to sex work to survive in the Dominican Republic ( 31 ).…”
Section: Responding To Sensitive Issues Among Migrants: Abortion and ...mentioning
confidence: 99%
“…Restrepo Pineda et al observaron que el uso de preservativos no era sistemático en los trabajadores sexuales en general, y aún menos probable en los trabajadores sexuales masculinos venezolanos, cuya precaria situación financiera los llevaba a prácticas más riesgosas, pero más rentables ( 30 ). Paulino Ramírez et al expusieron sentimientos de depresión y aislamiento en las personas migrantes de Venezuela que recurren al trabajo sexual para sobrevivir en República Dominicana ( 31 ).…”
Section: Responder a Cuestiones Delicadas Relativas A Las Personas Mi...unclassified